The Role of Culturally Responsive Teaching (CRT) in Contextual Teaching and Learning to Improve Students' Scientific Explanation Skills - Lailatul Mardhiyyah; Habiddin Habiddin; Rudiyanto Rudiyanto (J-PEK (Jurnal Pembelajaran Kimia), 2025)
A scientific explanation is vital for students, but they often lack access to one. They seldom apply their knowledge to elucidate natural phenomena, leading to a basic and less meaningful understanding. To enhance students' abilities to provide scientific explanations, the culturally responsive teaching (CRT) approach is employed in science education. This pre-experimental pre-test post-test study involved seven students at a private junior high school in Malang. Written tests, including pre-tests and post-tests, were used to evaluate the improvement of students' scientific explanation skills. The study indicates a significant enhancement in students' scientific explanations, categorizing them in the medium range. This finding emphasizes the necessity to implement the CRT approach in broader educational contexts.References Acebes, E. I., & Taber, K. S. (2024). Secondary Science Teachers’ Instructional Strategies for Promoting the Construction of Scientific Explanations. Science & Education, 33(4), 853–899. https://doi.org/10.1007/s11191-022-00412-5 Ariawan, I. B. A. M., Lestari, N. A. P., & Dharma, I. M. A. (2022). Pembelajaran CTL (Contextual Teaching And Learning) Untuk Meningkatkan Hasil Belajar IPA. IRJE, 2(1). https://irje.org/index.php/irje Billings, G. L. (1995). Toward a Theory of Culturally Relevant Pedagogy. American Educational Research Journal, 32(3), 465–491. https://doi.org/10.3102/00028312032003465 Braaten, M., & Windschitl, M. (2011). Working toward a stronger conceptualization of scientific explanation for science education. Science Education, 95(4), 639–669. Chin, C., & Brown, D. E. (2000). Learning in Science: A Comparison of Deep and Surface Approaches. Journal of Research in Science Teaching, 37(2), 109–138. Fadillah, L. R., & Listiawan, T. (2024). Implementasi Pendekatan Culturally Responsive Teaching (CRT) pada Pembelajaran IPA untuk Meningkatkan Motivasi Belajar Peserta Didik di SMP. Journal of Innovation and Teacher Professionalism, 2(1), 65–73. https://doi.org/10.17977/um084v2i12024p65-73 Gay, G. (2000). Culturally Responsive Teaching: Theory, Research, and Practice, Third Edition. Teacher College Press. Habiddin, H., Atikah, A., Husniah, I., Haetami, A., & Maysara, M. (2021). Building scientific explanation: A study of acid-base properties of salt solution. AIP Conference Proceedings, 2330(1), 20047. https://doi.org/10.1063/5.0043215 Hake, R. R. (1998). Interactive-engagement versus traditional methods: A six-thousand-student survey of mechanics test data for introductory physics courses. American Journal of Physics, 66(1), 64–74. https://doi.org/10.1119/1.18809 Islakhiyah, Sutopo, & Yulianti, L. (2018). Scientific Explanation of Light through Phenomenon-based Learning on Junior High School Student. First International Conference on Science, Mathematics, and Education (ICoMSE), 218(1), 173-185. Khasanah, I. M., Nuroso, H., & Pramasdyahsari, A. S. (2023). Efektivitas Pendekatan Culturally Responsive Teaching (CRT) untuk Meningkatkan Hasil Belajar Siswa Kelas II Sekolah Dasar. Edu Society: Jurnal Pendidikan, Ilmu Sosial Dan Pengabdian Kepada Masyarakat, 3(3), 1121–1127. Laughter, J. C., & Adams, A. D. (2012). Culturally Relevant Science Teaching in Middle School. Urban Education, 47(6), 1106–1134. https://doi.org/10.1177/0042085912454443 Madkins, T. C., & Royston, M. M. de. (2019). Illuminating political clarity in culturally relevant science instruction. Science Education, 103(6), 1319–1346. https://doi.org/https://doi.org/10.1002/sce.21542 McNeill, K. L., & Krajcik, J. (2008). Scientific Explanations: Characterizing and Evaluating the Effects of Teachers’ Instructional Practices on Student Learning. Journal of Research in Science Teaching, 45(1), 53–78. McNeill, K. L., Lizotte, D. J., & Krajcik, J. (2006). Supporting Students’ Construction of Scientific Explanations by Fading Scaffolds in Instructional Materials. Journal of The Learning Sciences, 15(2), 153–191. Nafiah, N. I., Damayanti, A., Winarno, A. N. P., Akmalia, D. R., Nurdaningrum, F., Azizah, F. A., Juditha, I., Widya, I. S., Afnia, M. N., & Martiningrum, R. (2025). Learning Approach for Enhancing Students’ Creativity. STEM Education International, 1(1), 29–35. https://doi.org/10.71289/wrycf010 Sampson, V., Grooms, J., & Walker, J. P. (2011). Argument-Driven Inquiry as A Way to Help Students Learn How to Participate in Scientific Argumentation and Craft Written Arguments: An Exploratory Study. Science Education, 95(2), 217–257. Sandoval, W. A., & Reiser, B. J. (2004). Explanation-driven inquiry: Integrating conceptual and epistemic scaffolds for scientific inquiry. Science Education, 88(3), 345–372. Sari, A., Sari, Y. A., & Namira, D. (2023). Penerapan Model Pembelajaran Problem Based Learning Terintegrasi Culturally Responsive Teaching (CRT) Untuk Meningkatkan Motivasi Dan Hasil Belajar Siswa Kelas X IPA 2 SMA Negeri 7 Mataram Pada Mata Pelajaran Kimia Tahun Ajaran 2022/2023. Jurnal Asimilasi Pendidikan, 2, 110–118. http://asimilasi.journalilmiah.org. Sexton, S. S. (2024). Culturally responsive teaching through primary science in Aotearoa New Zealand. London Review of Education, 22(1), 4. Trianto. (2007). Model-Model Pembelajaran Inovatif Berorientasi Konstruktivistik. Prestasi Pustaka Publisher. Wang, C.-Y. (2015). Scaffolding Middle School Students’ Construction of Scientific Explanations: Comparing a cognitive versus a metacognitive evaluation approach. International Journal of Science Education, 37(2), 237–271. https://doi.org/10.1080/09500693.2014.979378 Wijayanto, T., Supeno, S., & Bektiarso, S. (2020). Pengaruh Model Inkuiri Terstruktur terhadap Kemampuan Scientific Explanation Siswa dalam Pembelajaran Fisika di SMA. Jurnal Pendidikan Fisika Tadulako Online, 8(2), 18–24.